2016
DOI: 10.5539/ijef.v8n9p91
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corruption on Economic Growth in OIC Countries

Abstract: Economic growth in a country can be attributed to many variables, both positive and negative. Raising the level of human capital, openness and investment are examples of factors typically considered to have a positive impact on economic progress, while corruption is one of the factors that are often seen as detrimental to economic growth. The purpose of this study is to analyse whether the levels of perceived corruption in a cross-section of countries have affected their economic growth rates over the years [2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
(36 reference statements)
1
11
2
Order By: Relevance
“…This result rejects the hypothesis formulated in the study that corruption is negatively related to economic growth. This is different from the findings of Ertimi et al (2016) which states that corruption affects the decline in economic growth. But the corruption variable is not a variable that significantly influences economic growth during the observation period.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This result rejects the hypothesis formulated in the study that corruption is negatively related to economic growth. This is different from the findings of Ertimi et al (2016) which states that corruption affects the decline in economic growth. But the corruption variable is not a variable that significantly influences economic growth during the observation period.…”
Section: Resultscontrasting
confidence: 99%
“…Fourth, voting has a positive effect but then decreases. Ertimi et al (2016) analyzed the relationship between corruption and the economic growth rate in 14 OIC countries. This research uses quantitative methods and is analyzed using panel data regression.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result implies that the rate of corruption in Nigeria has a significant positive impact on economic growth of the country. This result agrees with the findings of (Damir & Petar, 2011;Ahmad, Ullah & Arfeen, 2012;Huang, 2012;Peev & Mueller, 2012) but conflicts with the studies of (Pulok, 2010;Diri, 2013;Maria et al, 2013;Nguyen, Nguyen & Binh, 2014;Nwankwo, 2014;Trabelsi & Trabelsi, 2014;Eritimi et al 2016;Adegboyega, 2017;Thach et al, 2017) who found that corruption influences economic growth negatively.…”
Section: Regression Resultssupporting
confidence: 84%
“…The empirical result revealed that corruption impact on economic growth most in zone 2 period which is the medium term period. Eritimi et al (2016) examined the impact of corruption on economic growth of 14 Organization of Islamic Cooperation (OIC) from 2003 to 2010. The study employed endogenous growth theory and economic freedom index for analysis.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation